The Impact of Participation in Community Support Groups on the Psychological Well-Being of Type II Diabetes Patients - Nuari, Nian Afrian; Aini, Efa Nur (Fakultas Kedokteran, Universitas Papua, 2025)
Psychological well-being is one of the most important aspects in improving the quality of life of individuals, especially for people with chronic diseases such as Type II Diabetes Mellitus. People with diabetes often face various challenges, both physically and psychologically, which can have an impact on their quality of life. The purpose of this study was to determine the effect of Community Support Groups (CSG) on psychological well-being. The design of this study was a pre-experiment with a pretest-posttest approach. The sample of this study was patients with Type II Diabetes Mellitus using purposive sampling obtained 19 respondents. Data collection using a questionnaire sheet and analyzed using the Paired T-Test. The results of the study before the intervention were given, most (52.64%) respondents had psychological well-being with a score range of 42-84. After being given the intervention, almost most respondents (52.64%) had psychological well-being with a score range of 85-126. The results of the analysis showed that there was an effect of CSG on psychological well-being (p-value = 0.000). The implementation of CSG intervention effectively provides a place for individuals who are members to provide social support to each other, share experiences and feel accepted in the group can reduce stress, increase self-control, and strengthen life expectancy. So it is hoped that CSG can be an effective strategy to improve the psychological well-being of individuals with chronic diseases